Self-reporting joule heating modulated stiffness of polymeric nanocomposites for shape reconfiguration - Ji, Shaobo (2023)
Shape reconfigurable devices, e.g., foldable phones, have emerged with the development of flexible electronics. But their rigid frames limit the feasible shapes for the devices. To achieve freely changeable shapes yet keep the rigidity of devices for user-friendly operations, stiffness-tunable materials are desired, especially under electrical control. However, current such systems are multilayer with at least a heater layer and a structural layer, leading to complex fabrication, high cost, and loss of reprocessability. Herein, we fabricate covalent adaptable networks-carbon nanotubes (CAN-CNT) composites to realize Joule heating controlled stiffness. The nanocomposites function as stiffness-tunable matrices, electric heaters, and softening sensors all by themselves. The self-reporting of softening is used to regulate the power control, and the sensing mechanism is investigated by simulating the CNT-polymer chain interactions at the nanoscale during the softening process. The nanocomposites not only have adjustable mechanical and thermodynamic properties but also are easy to fabricate at low cost and exhibit reprocessability and recyclability benefiting from the dynamic exchange reactions of CANs. Shape and stiffness control of flexible display systems are demonstrated with the nanocomposites as framing material, where freely reconfigurable shapes are realized to achieve convenient operation, wearing, or storage, fully exploiting their flexible potential.